2014
DOI: 10.1111/1574-6941.12421
|View full text |Cite
|
Sign up to set email alerts
|

Off-site impacts of agricultural composting: role of terrestrially derived organic matter in structuring aquatic microbial communities and their metabolic potential

Abstract: While considered as sustainable and low-cost agricultural amendments, the impacts of organic fertilizers on downstream aquatic microbial communities remain poorly documented. We investigated the quantity and quality of the dissolved organic matter leaching from agricultural soil amended with compost, vermicompost or biochar and assessed their effects on lake microbial communities, in terms of viral and bacterial abundances, community structure and metabolic potential. The addition of compost and vermicompost s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 57 publications
2
6
0
Order By: Relevance
“…In contrast, the richness of the bacterial communities in the reservoir water and soil only treatments remained unchanged and evenness of the communities increased between T i and T f ( Figure 3 ). DOC serves as an important substrate and energy source for heterotrophic bacteria ( del Giorgio and Davis, 2003 ; Wei et al, 2015a ) and the metabolic activity of the community is controlled by DOC quantity and quality and, hence, carbon source ( Pommier et al, 2014 ). In our experiment, the DOC additions in the reservoir water were principally from phytoplankton production (an autochthonous source), whereas in all the other treatments, DOC inputs were initially from soils (allochthonous) and after 6 days from primary production (autochthonous).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the richness of the bacterial communities in the reservoir water and soil only treatments remained unchanged and evenness of the communities increased between T i and T f ( Figure 3 ). DOC serves as an important substrate and energy source for heterotrophic bacteria ( del Giorgio and Davis, 2003 ; Wei et al, 2015a ) and the metabolic activity of the community is controlled by DOC quantity and quality and, hence, carbon source ( Pommier et al, 2014 ). In our experiment, the DOC additions in the reservoir water were principally from phytoplankton production (an autochthonous source), whereas in all the other treatments, DOC inputs were initially from soils (allochthonous) and after 6 days from primary production (autochthonous).…”
Section: Discussionmentioning
confidence: 99%
“…Although the positive impacts of organic amendments on soil quality and crop yield in both temperate and tropical countries have been amply demonstrated, the impact of these amendments on soil runoff and the impact of that runoff on adjacent aquatic systems has been less studied. The concentration of dissolved organic carbon (DOC) in soil runoff is strongly influenced by soil organic carbon content, soil erosion, vegetation cover, amounts, and intensities of rainfall, as well as type of composting applied ( Mailapalli et al, 2012 ; Worrall et al, 2012 ; Janeau et al, 2014 ; Pommier et al, 2014 ). It is therefore important to understand the fate of this DOC, as runoff has the potential to impact adjacent terrestrial and/or aquatic ecosystems ( Jacinthe et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The export of matter from soils to an adjacent aquatic ecosystem is controlled, in part, by the type of plant cover present, the slope and the concentration of organic matter in the soils ( Magdoff and Weil, 2004 ; Podwojewski et al, 2008 ; Soupir and Mostaghimi, 2011 ; Janeau et al, 2014 ; Rochelle-Newall et al, 2014 ). Moreover, the export of organic matter and bacteria can be particularly high in sloping lands both of which can affect downstream aquatic ecosystems ( Ribolzi et al, 2011b ; Pommier et al, 2014 ). The impacts of agriculture on the ecosystem are therefore not expected to be the same in temperate and tropical systems.…”
Section: Impact Of Land-usementioning
confidence: 99%
“…This occurrence can be explained by the fact that in the second collection was characterized by an extremely dry season with intense heat, but light incidence of rain two days before the sampling unlike the other three periods. Recently, Pommier et al (2014) observed a significantly increased amount of dissolved organic carbon in the leachate from agricultural soil amended with compost and vermicompost compared to un-amended soil. They also observed that leachates from these amended soils were highly bioavailable to aquatic microbiota, reducing the metabolic potential of the microbial community and harboring specific communities.…”
Section: Microbiological Parametersmentioning
confidence: 99%